2021
DOI: 10.3390/ijms22094931
|View full text |Cite
|
Sign up to set email alerts
|

Effective Drug Concentration and Selectivity Depends on Fraction of Primitive Cells

Abstract: Poor efficiency of chemotherapeutics in the eradication of Cancer Stem Cells (CSCs) has been driving the search for more active and specific compounds. In this work, we show how cell density-dependent stage culture profiles can be used in drug development workflows to achieve more robust drug activity (IC50 and EC50) results. Using flow cytometry and light microscopy, we characterized the cytological stage profiles of the HL-60-, A-549-, and HEK-293-derived sublines with a focus on their primitive cell content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 87 publications
3
13
0
Order By: Relevance
“…3A). This is a documented phenomenon in cancer studies whereby a direct correlation has been drawn between starting cell densities and drug efficacy (31). In other works, TAT has documented measurable cytotoxicity above 10 µM (32) and our metabolic assays employed herein showed no to low cytotoxicity from TAT-CaM treatment only.…”
Section: Discussionsupporting
confidence: 68%
“…3A). This is a documented phenomenon in cancer studies whereby a direct correlation has been drawn between starting cell densities and drug efficacy (31). In other works, TAT has documented measurable cytotoxicity above 10 µM (32) and our metabolic assays employed herein showed no to low cytotoxicity from TAT-CaM treatment only.…”
Section: Discussionsupporting
confidence: 68%
“…Nonetheless, the equal values for N/C ratios in both our cell populations were relatively low; thus, together with the findings from their qualitative ultrastructural observations, it can be suggested that the progenitor cells exhibited the features of an advanced differentiation stage. This assumption can be supported by the findings of Lica et al (2021) who characterized three sublines of A-549 cell line based on many aspects considering also the N/C ratio as follows: Primitive (N/C: 0.9–0.6), Standard (N/C: 0.6–0.2), and Mature (N/C: 0.2–0.05).…”
Section: Discussionmentioning
confidence: 53%
“…Selectivity index is generated as a ratio of the lethal dose to the therapeutic dose of a given substance. The fibroblast and red blood cell IC 50 values represent the lethal dose (LD 50 ), while the IC 50 of a given drug is defined as the effective dose (ED 50 ) . An SI greater than or equal to 3 has been used as a criterion warranting continued studies of the candidate anticancer drug .…”
Section: Resultsmentioning
confidence: 99%